Report of the fourteenth working committee and general assembly ASEAN Inter-parliamentary organization - Asean inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 1993)
Hội nghị lần thứ mười bốn được tổ chức vào ngày 20 tháng 9, 1993 tại nhà Quốc hội, Kuala Lumpur.